Answer:
The coefficient ( ) of 5a is filled by
and the coefficient ( ) of a² is filled by ' 0 '
Explanation:
The given expression is 6a - ( )5a = ( )a² - 35a
To find the missing coefficient, compare the left and right side of expression,
First compare the 6a - ( )5a = - 35a
6a+35a = ( )5a
41a = ( )5a
divide both the sides by 5a,


The coefficient ( ) of 5a is filled by

Now, compare 0 = ( )a²
So, the coefficient ( ) of a² is filled by ' 0 '
Hence, The coefficient ( ) of 5a is filled by
and the coefficient ( ) of a² is filled by ' 0 '